Atomic diffusion processes in MgO/Fe/MgO multilayer - Singh, Jitendra Pal; Lim, Weon Cheol; Chae, Keun Hwa (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2015)
In present work, atomic diffusion processes in MgO/Fe/MgO structure is investigated. This structure is deposited by using e-beam evaporation method in ultra-high vacuum (10(-7) Torr). X-ray diffraction pattern exhibits amorphous nature of MgO layer, however, Au and Fe layers are polycrystalline in nature. Structural quality investigated using transmission electron microscopy shows the presence of short-ranged crystalline ordering in MgO layer. Oxygen atoms of this layer exhibit its interaction with Mg to form MgO, however, Fe layer exists in metal form with onset of oxidation at interface. Rutherford backscattering study shows the diffusion of atoms from upper layers to the layers underneath and to the substrate. Au atoms exhibit exponential diffusion profile in the structure, however, the compositional variation of Fe atoms is described using the combination of exponential decay and exponential growth functions. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: MAGNETIC-PROPERTIES; MGO; INTERFACE; FERRITE; XANES; LAYER